Analisis Pengaruh Kualitas Layanan Dan Citra Perusahaan Terhadap Keputusan Mengambil Kredit Produktif Pada Bank Jateng Dengan Kepercayaan Sebagai Variabel Mediasi (Studi Kasus pada Bank Jateng Cabang Pembantu Wanadadi Banjarnegara) - Nofa Hari Widayanto; Ali Mursid (Magister Manajemen STIE Bank BPD Jateng, 2022)
This study intends to analyze how service quality and corporate image influence customer decisions to take productive credit mediated by trust in Bank Jateng Wanadadi Sub-Branch. Productive credit customers were used as the population in this study, which consisted of KLKK (Employee Cooperative Credit Linkage) customers, KWU (Enterprise Credit), KUP (Productive Business Credit), MSME and Cooperative Credit, Extra Credit, Mitra Jateng 25 Credit, and KUR (KUR). Samples were taken through non-probability sampling method using saturated samples. Respondents were 162 customers who were used as samples. Data analysis used SEM analysis, bootstrapping method, and VAF method. The results of the study indicate that (1) the customer's decision to take productive credit at Bank Jateng Wanadadi Sub-Branch is influenced by service quality; (2) the customer's decision to take productive credit at Bank Jateng Wanadadi Sub-Branch is not influenced by the company's image; (3) service quality affects customer trust in Bank Jateng Wanadadi Sub-Branch; (4) corporate image affects customer trust in Bank Jateng Wanadadi Sub-Branch; (5) the customer's decision to take productive credit at Bank Jateng Wanadadi Sub-Branch is influenced by trust; (6) there is a mediating effect of trust on service quality in influencing customer decisions to take productive credit at Bank Jateng Wanadadi Sub-Branch; and (7) there is no mediating effect of trust on company image in influencing customer decisions to take productive credit at Bank Jateng Wanadadi Sub-Branch.